PENEGAKAN HUKUM OLEH SATUAN RESERSEK RIMINAL KEPOLISIAN RESOR KOTA PEKANBARU TERHADAP TINDAKPIDANA HUMAN TRAFFICKING DI WILAYAH KOTA PEKANBARU - Andrew, Simon; Diana, Ledy; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
At this timethere are much human trafficking cases at Pekanbaru City. There’s much ways for the human trafficking doer to do their crime. This causes trouble for the society, because that kind of crime makes the society lose their trust to each other even for their closest relatives. Anyone can become the victims of human trafficking, men, women, rich people, poor people, old and even the young people and can be happened everytime and everywhere. According to the writer’s data from his research at Police Department of Pekanbaru City which research at 2014 and 2015 started from December 11th 2014 LP/K/1511/XII/2014/RESKRIM as its report number that The Police Department of Pekanbaru City got a report that there is human trafficking case by AA as his initials. Second case happened at October 3rd 2015 with LP/K/1114/X/2015/RESKRIM as its reports number that the Police Department of Pekanbaru City got a report from the human trafficking victim which escaped from the human trafficking doer by DN as his initials.The problems discussed are the First, how enforcement by the police against the crime of human trafficking. Second, what are the factors that cause the crime human tarfficking in Pekanbaru Police.The method used is empirical research, another term is sociological research is also called field research and descriptive research. In collecting the data, the type of data used in this study are primary data and secondary data, ie directly through written records and interviews with the Chief of Unit IV of the Criminal Investigation Police Pekanbaru, Act No. 21 of 2007 concerning the eradication of human trafficking. The data analysis was done qualitatively and conclusions drawn deductively.From the results of research by the author that enforcement by the police has not done well because still have a human trafficking crime shrouded in Pekanbaru city.Keywords: Crime –Human Trafficking –